МЕТОДОЛОГІЧНІ ЗАСАДИ ПОШУКУ СОЦІАЛЬНОГО ВИМІРУ ЗНАННЯ - Чмихун, С. Є. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
У статті розглянуті деякі найпоширеніші методологічні стратегії дослідження феноменасоціального знання, які пов’язані з утвердженням постнекласичної раціональності. Методологічністратегії в дослідженні феномена сучасного соціального знання визначаються в культур-центристську,ненатуралістичну, програмно-аналітичну й системну стратегії залежно від вихідних підстав: культурних,природних, соціогуманітарних або довільно систематизованих.Cmihun S. METHODOLOGICAL STRATEGIES OF SEARCH OF SOCIAL DIMENSION OFKNOWLEDGE. This article describes the most widespread research methodological strategies of social knowledge.They arise from the statement on dependence of scientific achievements with social conditions. They reconsidertraditional philosophic interpretations of basic phenomena in gnoseology and epistemology such as truth andpractice. Methodological strategy in research of modern social knowledge phenomenon is defined in culturecentered,non-naturalistic, program-analytic and system depending on initial bases.Key words: social knowledge, methodological strategies.Чмихун С. МЕТОДОЛОГИЧЕСКИЕ СТРАТЕГИИ ПОИСКА СОЦИАЛЬНОГО ИЗМЕРЕНИЯЗНАНИЯ. В статье рассмотрены некоторые наиболее влиятельные сегодня методологические стратегииисследования феномена социального знания, которые связаны с утверждением постнеклассическойрациональности. Методологические стратегии в исследовании феномена современного социального знанияопределяется в культур-центристскую, ненатуралистическую, программно-аналитическую и системную взависимости от исходных оснований: культурных, естественных, социогуманитарных или свободносистематизированных.Ключевые слова: социальное познание, методологические стратегии.